2014
DOI: 10.4184/asj.2014.8.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Comparison of Posterolateral Fusion and Posterior Interbody Fusion Techniques for Multilevel Lumbar Spinal Stabilization In Manual Workers

Abstract: Study DesignEighty-four patients who had been treated for degenerative spinal diseases between January 2006 and June 2009 were reviewed retrospectively.PurposeWe aimed to compare the clinical and radiologic findings of manual workers who underwent posterolateral fusion (PLF) or posterior interbody fusion (PLIF) involving fusion of 3 or more levels of the spine.Overview of LiteraturePrevious studies have concluded that there is no significant difference between the clinical outcome of PLF and PLIF techniques.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
2
16
4
Order By: Relevance
“…The findings of our study showed that the improvement in LBP during the follow-up was significantly more in the patients who were operated on using PLF with posterior instrumentation than in the patients operated on with PLIF with posterior instrumentation and more LBP was seen in the patients of Group II after the operation. The results in our study are somewhat in contrast to other studies showing that there is a similar outcome between PLF and PLIF (13)(14)(15)(38)(39)(40)(41)(42)(43). Ekman et al (39) compare the outcome of PLIF and PLF in adult isthmic spondylolisthesis (IS) and reported that type of fusion, PLIF or PLF, does not affect the pain at 2 years after surgical treatment of adult IS.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of our study showed that the improvement in LBP during the follow-up was significantly more in the patients who were operated on using PLF with posterior instrumentation than in the patients operated on with PLIF with posterior instrumentation and more LBP was seen in the patients of Group II after the operation. The results in our study are somewhat in contrast to other studies showing that there is a similar outcome between PLF and PLIF (13)(14)(15)(38)(39)(40)(41)(42)(43). Ekman et al (39) compare the outcome of PLIF and PLF in adult isthmic spondylolisthesis (IS) and reported that type of fusion, PLIF or PLF, does not affect the pain at 2 years after surgical treatment of adult IS.…”
Section: Discussioncontrasting
confidence: 99%
“…Lidar et al (42) reported that there was no difference regarding VAS between the 2 groups. However, in contrast to our findings, some studies have reported that PLIF provides more reduction in VAS than PLF (15,43). In 2015, Alijani et al (15) evaluated and compared the pain of patients with spondylolisthesis who had undergone either PLF or PLIF and they reported that PLIF was related to better outcome with respect to pain control at 6 month after the surgery than PLF.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Radiographic fusion was assessed using plain radiographs by Lenke classification for PLF and by Brantigan, Steffee, Fraser (BSF) classification for TLIF group. 11…”
Section: Outcomes Measuresmentioning
confidence: 99%